Lignocellulosic Biomass Transformations via Greener Oxidative Pretreatment Processes: Access to Energy and Value-Added Chemicals - Den, Walter; Sharma, Virender K.; Lee, Mengshan; Nadadur, Govind; Varma, Rajender S. (Frontiers in Chemistry, 2018)
Anthropogenic climate change, principally induced by the large volume of carbon dioxide emission from the global economy driven by fossil fuels, has been observed and scientifically proven as a major threat to civilization. Meanwhile, fossil fuel depletion has been identified as a future challenge. Lignocellulosic biomass in the form of organic residues appears to be the most promising option as renewable feedstock for the generation of energy and platform chemicals. As of today, relatively little bioenergy comes from lignocellulosic biomass as compared to feedstock such as starch and sugarcane, primarily due to high cost of production involving pretreatment steps required to fragment biomass components via disruption of the natural recalcitrant structure of these rigid polymers; low efficiency of enzymatic hydrolysis of refractory feedstock presents a major challenge. The valorization of lignin and cellulose into energy products or chemical products is contingent on the effectiveness of selective depolymerization of the pretreatment regime which typically involve harsh pyrolytic and solvothermal processes assisted by corrosive acids or alkaline reagents. These unselective methods decompose lignin into many products that may not be energetically or chemically valuable, or even biologically inhibitory. Exploring milder, selective and greener processes, therefore, has become a critical subject of study for the valorization of these materials in the last decade. Efficient alternative activation processes such as microwave- and ultrasound irradiation are being explored as replacements for pyrolysis and hydrothermolysis, while milder options such as advanced oxidative and catalytic processes should be considered as choices to harsher acid and alkaline processes. Herein, we critically abridge the research on chemical oxidative techniques for the pretreatment of lignocellulosics with the explicit aim to rationalize the objectives of the biomass pretreatment step and the problems associated with the conventional processes. The mechanisms of reaction pathways, selectivity and efficiency of end-products obtained using greener processes such as ozonolysis, photocatalysis, oxidative catalysis, electrochemical oxidation, and Fenton or Fenton-like reactions, as applied to depolymerization of lignocellulosic biomass are summarized with deliberation on future prospects of biorefineries with greener pretreatment processes in the context of the life cycle assessment.